Combining Pre-operative Diffusion Tensor Images and Intraoperative Magnetic Resonance Images in the Navigation Is Useful for Detecting White Matter Tracts During Glioma Surgery - Tamura, Manabu; Kurihara, Hiroyuki; Saito, Taiichi; Nitta, Masayuki; Maruyama, Takashi; Tsuzuki, Shunsuke; Fukui, Atsushi; Koriyama, Shunichi; Kawamata, Takakazu; Muragaki, Yoshihiro (Frontiers in Neurology, 2022)
Purpose: We developed a navigation system that superimposes the fractional anisotropy (FA) color map of preoperative diffusion tensor imaging (DTI) and intraoperative magnetic resonance imaging (MRI). The current study aimed to investigate the usefulness of this system for neurophysiological monitoring and examination under awake craniotomy during tumor removal. Method: A total of 10 glioma patients (4 patients with right-side tumors; 5 men and 5 women; average age, 34 years) were evaluated. Among them, the tumor was localized to the frontal lobe, insular cortex, and parietal lobe in 8, 1, and 1 patient, respectively. There were 3 patients who underwent surgery on general anesthesia, while 7 patients underwent awake craniotomy. The index of DTI anisotropy taken preoperatively (magnetic field: 3 tesla, 6 motion probing gradient directions) was analyzed as a color map (FA color map) and concurrently co-registered in the intraoperative MRI within the navigation. In addition to localization of the bipolar coagulator and the cortical stimulator for brain mapping on intraoperative MRI, the preoperative FA color map was also concurrently integrated and displayed on the navigation monitor. This white matter nerve functional information was confirmed directly by using neurological examination and referring to the electrophysiological monitoring. Results: Intraoperative MRI, integrated preoperative FA color map, and microscopic surgical view were displayed on one screen in all 10 patients, and white matter fibers including the pyramidal tract were displayed as a reference in blue. Regarding motor function, motor-evoked potential was monitored as appropriate in all cases, and removal was possible while directly confirming motor symptoms under awake craniotomy. Furthermore, the white matter fibers including the superior longitudinal fasciculus were displayed in green. Importantly, it was useful not only to localize the resection site, but to identify language-related, eye movement-related, and motor fibers at the electrical stimulation site. All motor and/or language white matter nerve fibers were identified and visualized with the co-registration and then with an acceptable post-operative neurological outcome. Conclusion: Co-registering an intraoperative MR images and a preoperative FA color map is a practical and useful method to predict the localization of critical white matter nerve functions intraoperatively in glioma surgery.